Band Wear and Effects on Recovery and Survival Estimates of Diving Ducks - Michael L. Szymanski; Todd W. Arnold; Pamela R. Garrettson; Alan D. Afton (Wildlife Society Bulletin)
ABSTRACT Wildlife biologists commonly use marked individuals to estimate population size and vital rates. If markers are lost or become too illegible to be reported (which we define as functional loss), population size and vital rates derived from marked individuals could be biased. We double‐banded 4,990 lesser scaup (Aythya affinis) and 1,429 redheads (A. americana) with a traditionally used band made of aluminum, plus another band made of incoloy designed to be more resistant to wear. Banding took place at 10 late‐summer banding stations in the northcentral United States and Canada during 2009 and 2010 and during spring at Pool 19 on the Mississippi River, Iowa, USA, during 2009–2011. We then examined bands recovered from hunter‐shot birds to assess wear of paired bands. We also conducted band‐recovery analyses to test for differences in band retention and reporting rates between birds banded with aluminum versus hard metal bands. Band wear assessments indicated that incoloy bands lost zero mass over time and showed no effects of wear. Although no bands were lost, aluminum bands showed significant mass loss and wear over time. For double‐banded lesser scaup recovered in their fourth year after banding, 71.9% of aluminum bands had contact information that was completely unreadable, compared with only 12.5% for those worn by redheads. Based on our recent double‐band recovery data, up to 34% of lesser scaup bands would be recovered during the fifth through eighth hunting seasons of band wear. Band wear affected estimated recovery rates of both species, with stronger effects in lesser scaup. Our results indicate that use of aluminum bands resulted in a substantial loss of information; thus, banders should only use bands made of hard metal alloys (e.g., incoloy or stainless steel), and discontinue all use of aluminum bands for these species and other diving ducks with sparse recovery data. Future demographic analyses using banding data for species with excessive band wear and low numbers of band‐recoveries should account for band type and functional band loss. © 2020 The Wildlife Society.